1998
DOI: 10.1345/aph.17302
|View full text |Cite
|
Sign up to set email alerts
|

Selective Serotonin-Reuptake Inhibitor–Induced Movement Disorders

Abstract: SSRI use appears to be associated with the development of movement disorders, as either a direct result of the drug or exacerbation of an underlying condition. Predisposing factors may include the use of neuroleptics, existing neurologic diagnoses, or preexisting movement disorders. Clinicians should be cognizant of the potential for these reactions, as prompt recognition and management is essential in preventing potentially significant patient morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(134 citation statements)
references
References 34 publications
2
125
0
7
Order By: Relevance
“…It may also explain the increased incidence of depression preceding the diagnosis of PD, because of the fact that pathophysiological compensatory mechanisms are already in action long before clinical symptoms become apparent (Leentjens et al, 2003b). Finally, it may provide an explanation for the exacerbation of extrapyramidal symptoms that occur in some PD patients treated with selective serotonin reuptake inhibitors (SSRIs) (Leo, 1996;Gerber and Lynd, 1998). In spite of the fact that this hypothesis was launched in 1984, to date it has not been experimentally verified.…”
Section: Introductionmentioning
confidence: 99%
“…It may also explain the increased incidence of depression preceding the diagnosis of PD, because of the fact that pathophysiological compensatory mechanisms are already in action long before clinical symptoms become apparent (Leentjens et al, 2003b). Finally, it may provide an explanation for the exacerbation of extrapyramidal symptoms that occur in some PD patients treated with selective serotonin reuptake inhibitors (SSRIs) (Leo, 1996;Gerber and Lynd, 1998). In spite of the fact that this hypothesis was launched in 1984, to date it has not been experimentally verified.…”
Section: Introductionmentioning
confidence: 99%
“…Двойных слепых исследований влия-ния пероральных медикаментов на эти симптомы не про-водилось. Ряд лекарственных препаратов, влияющих на некоторые проявления дистонии или сопутствующие заболевания, например нейролептики или антидепрес-санты из группы селективных ингибиторов серотонина, могут ухудшать течение дистонии [62].…”
Section: лечениеunclassified
“…In complimation of the articles, akathisia is reported as the most extrapyramidal side effect in relation with SSRI after dystonia. 68,69 Gerber et al 69 have identified 127 extrapyramidal symptoms induced with SSRI. 19 of these symptoms are described as dystonia.…”
Section: Antidepressants Tricyclic Antidepressant Agents (Tcas)mentioning
confidence: 99%